Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Synthesis and characterization of cobalt substituted zinc ferri-chromites prepared by sol-gel auto-combustion method - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Patil, R. P.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Mixed metal oxides having spinel structure shows interesting structural properties. In the present investigation, cobalt substituted zinc ferri-chromites were prepared by sol-gel auto-combustion method. The completion of solid state reaction and the formation of spinel phase were identified using X-ray diffraction technique. All the compounds exhibit cubic spinel symmetry and lattice constant shows an irregular trend with substitution of Co. Infra-red spectral studies shows an two strong bands, one around 600 cm(-1) which is attributed to the intrinsic vibrations of tetrahedral complexes and the other at 400 cm(-1) is due to octahedral one. The morphology and size of the particles was found out by scanning electron microscopy while the elemental compositions by elemental dispersive X-ray spectroscopy. The various compounds of the present system Zn1-xCoxFeCrO4 were also investigated for their thermal and electronic studies.